Mechanobiological evaluation of solid and multiple porous humeral stem architectures in reverse shoulder arthroplasty based on design and materials: a finite element study - John, Pearline Beulah; Nageswaran, Sharmila (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionStress shielding is a major cause of radiological changes in the humeral component, which is commonly evident in cementless stems of reverse shoulder implants. The bulkiness of the humeral stem results in less load being transmitted to the bone, curtailing bone remodeling. Designing an implant with adequate strength and a suitable material that matches the mechanical properties of bone can help prevent the implant migration or loosening, thereby lowering bone resorption.MethodsHumeral stems with no porosity and varied porosities, such as circular, elliptical, and trabecular architecture, were designed using 316L stainless steel and titanium alloy (Ti6Al4V). Finite element analysis (FEA) was conducted on eight bone–implant assemblies under four loading conditions for cortical and trabecular bones. Weighted mean of von Mises stress and mechanobiology associated with the strain energy densities were studied. This serves as a precursor in predicting the effect of stress shielding.ResultsThe titanium implant with trabecular architecture was mechanically close to the intact bone compared to the other varied porosity designs. It also had better load-bearing capacity than the solid stems.DiscussionThese investigations help understand the load-bearing capacity of reverse shoulder humeral stems and ascertain the importance of combining the design and material in enhancing implant stability and longevity.